Fostering oral presentation competence through a virtual reality-based task for delivering feedback - van Ginkel, Stan; Gulikers, Judith; Biemans, Harm; Noroozi, Omid; Roozen, Mila; Bos, Tom; van Tilborg, Richard; van Halteren, Melanie; Mulder, Martin (Computers and education, 2019)
While previous studies have stressed the importance of feedback delivered by experts, it is unclear whether students' oral presentation competence can be fostered through innovative technology for delivering feedback. This experimental study examined the effectiveness of a virtual reality-based task, in which first-year undergraduate students practiced their presentation in a virtual environment and received feedback produced by the system, on their presentation competence components (i.e. cognition, behaviour and attitudes towards presenting). The effects were compared with a control condition, which was a face-to-face presentation task with expert feedback. The students’ performance was measured using pre- and post-test multiple-choice tests, validated rubrics, and self-evaluation instruments. Results revealed significant improvements from pre-test to post-test in all three presentation competence components, without a difference between the conditions. Furthermore, the self-evaluation tests showed that students who presented in virtual reality were appreciative of the detailed and analytical feedback they received. Because of sample size limitations, the effects found could not be generalised. Therefore, future research on a larger sample is needed to examine population effects. Follow-up studies should focus on the extent to which virtual reality-based tasks can encourage self-regulation skills for the effective and efficient integration of these tasks in presentation courses. •Students' presentation competence increased without a difference between VR and face-to-face.•Students who presented in virtual reality perceived the feedback as detailed.•Students who presented face-to-face perceived the feedback as constructive.